2023
DOI: 10.1371/journal.pone.0280835
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive phases and variability of vibration-induced postural reactions highlighted by center of pressure analysis

Abstract: Background The vibration-induced postural reaction paradigm (VIB-PR) offers a unique way for investigating sensorimotor control mechanisms. Measures of VIB-PR are usually calculated from the whole VIB period, yet recent evidence proposed that distinctive mechanisms are likely at play between the early vs. later phases of the postural reaction. Objectives The present work verified if spatiotemporal analyses of center of pressure (COP) displacements can detect differences between these early/later phases of VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Also, Kadri et al found that these patterns varied between and within individuals. The neurophysiological and behavioral correlates of these observations remain unknown (Kadri et al, 2020 , 2023 ), calling for further fundamental work with neurologically and physically healthy individuals. In terms of knowledge gaps, however, our review highlights a greater need for studies testing VIB-PR with other populations than healthy adults.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, Kadri et al found that these patterns varied between and within individuals. The neurophysiological and behavioral correlates of these observations remain unknown (Kadri et al, 2020 , 2023 ), calling for further fundamental work with neurologically and physically healthy individuals. In terms of knowledge gaps, however, our review highlights a greater need for studies testing VIB-PR with other populations than healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it might be easier to compare their findings to previous results obtained from the same muscles/tendons. However, different patterns of VIB-PR have been observed when targeting the tibialis anterior tendons vs. the Achilles tendon (Kadri et al, 2023 ), which puts into question why only the Achilles tendons are chosen in most studies. Testing other musculotendinous structures would give a more complete picture of regulatory mechanisms involved in keeping balance in different directions and using different joints.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations